Growth and characterization of AlGaN/GaN/AlGaN double-heterojunction high-electron-mobility transistors on 100-mm Si(111) using ammonia-molecular beam epitaxy - Ravikiran, L. (2015)
To improve the confinement of two-dimensional electron gas (2DEG) in AlGaN/GaN high electron mobility transistor (HEMT) heterostructures, AlGaN/GaN/AlGaN double heterojunction HEMT (DH-HEMT) heterostructures were grown using ammonia-MBE on 100-mm Si substrate. Prior to the growth, single heterojunction HEMT (SH-HEMT) and DH-HEMT heterostructures were simulated using Poisson-Schrödinger equations. From simulations, an AlGaN buffer with “Al” mole fraction of 10% in the DH-HEMT was identified to result in both higher 2DEG concentration (∼1013 cm−2) and improved 2DEG confinement in the channel. Hence, this composition was considered for the growth of the buffer in the DH-HEMT heterostructure. Hall measurements showed a room temperature 2DEG mobility of 1510 cm2/V.s and a sheet carrier concentration (ns) of 0.97 × 1013 cm−2 for the DH-HEMT structure, while they are 1310 cm2/V.s and 1.09 × 1013 cm−2, respectively, for the SH-HEMT. Capacitance-voltage measurements confirmed the improvement in the confinement of 2DEG in the DH-HEMT heterostructure, which helped in the enhancement of its room temperature mobility. DH-HEMT showed 3 times higher buffer break-down voltage compared to SH-HEMT, while both devices showed almost similar drain current density. Small signal RF measurements on the DH-HEMT showed a unity current-gain cut-off frequency (f T) and maximum oscillation frequency (f max) of 22 and 25 GHz, respectively. Thus, overall, DH-HEMT heterostructure was found to be advantageous due to its higher buffer break-down voltages compared to SH-HEMT heterostructure.